2020
DOI: 10.3389/fnhum.2020.600995
|View full text |Cite
|
Sign up to set email alerts
|

tVNS Increases Liking of Orally Sampled Low-Fat Foods: A Pilot Study

Abstract: Recently a role for the vagus nerve in conditioning food preferences was established in rodents. In a prospective controlled clinical trial in humans, invasive vagus nerve stimulation shifted food choice toward lower fat content. Here we explored whether hedonic aspects of an orally sampled food stimulus can be modulated by non-invasive transcutaneous vagus nerve stimulation (tVNS) in humans. In healthy participants (n = 10, five women, 20–32 years old, no obesity) we tested liking and wanting ratings of food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Intriguingly, we also observed a decrease in pre-drink motivation to consume the drink ("wanting") after nVNS in cymba conchae. This is in agreement with the observation that nVNS increases drive to obtain less-wanted prospective food rewards [22] and increases liking of less-liked low-fat puddings [21]. Other studies have not shown effects of increases in liking or wanting of food (images) in healthy controls [42,43].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Intriguingly, we also observed a decrease in pre-drink motivation to consume the drink ("wanting") after nVNS in cymba conchae. This is in agreement with the observation that nVNS increases drive to obtain less-wanted prospective food rewards [22] and increases liking of less-liked low-fat puddings [21]. Other studies have not shown effects of increases in liking or wanting of food (images) in healthy controls [42,43].…”
Section: Discussionsupporting
confidence: 90%
“…Liking and wanting ratings of food images were not affected in healthy controls, but in participants with major depressive disorder liking ratings increased under concurrent nVNS in cymba conchae. We previously showed an effect of concurrent nVNS in cymba conchae on liking of orally sampled foods, such that liking of low-fat puddings, but not of high-fat puddings, was increased [21]. Food intake was not affected in this study.…”
Section: Introductionmentioning
confidence: 45%
See 1 more Smart Citation
“…Since stimulation effects or differences between patients with MDD and HCP could be specific for certain types of food (Bodenlos et al, 2007;Öztürk et al, 2020), we performed an additional analysis only including food images and partitioned them according to their caloric density (high-caloric vs. low-caloric food) and taste quality (sweet vs. savory). We adapted our main model and included Caloric Density, Taste, and their interactions instead of the Image Type factor as within-subject factors.…”
Section: Ratingmentioning
confidence: 99%
“…In several studies, the reduction in weight loss and BMI achieved with vagal nerve therapy has been reported to improve obesity-associated medical problems, for example, diabetes and metabolic syndrome, with fewer risks than conventional bariatric surgery such as gastrointestinal leak, intra-abdominal bleeding, bowel obstruction, stricture, and ulceration [36,37]. Vagal nerve therapy is well tolerated, and there were no major adverse events stated in the literature [38][39][40][41][42][43]. Only mild or moderate events of nausea due to anaesthesia were reported [27].…”
Section: Discussionmentioning
confidence: 99%